Move in Time: Male Dancers of Indian Classical Dance in Malaysia - Premalatha Thiagarajan (Wacana Seni Journal of Arts Discourse, 2017)
Although the circulation of Indian music and dance existed since the early 1900s in colonial Malaya, the aesthetic visibility of Indian dance emerged in a more profound manner with the entrance of male gurus such as K. P. Bhaskar (1952), V. K. Sivadas (1952/53), and Gopal Shetty (1954). These masters not only opened the curtain of male dancing in Singapore/Malaya, but played imperative roles in creating awareness for Indian arts and culture by actively teaching and creating a variety Indian dances for the Malaysian audience. The trailblazers inspired other male dancers, who entered the dance scene in the following decades. The 1980s, particularly, saw the entrance of professionally trained multi-ethnic dancing men. While Indian classical dance forms such as Bharata Natyam in Malaysia were numerically dominated by women dance practitioners emerging from arangetram (solo debut) recitals, male dance artists stood as highly visible public performers enabled by technical prowess, innovative staging and choreographies, and media and audience support. This paper traces a non-linear historical genealogy of Indian dance in Malaysia by drawing materials from archival study and ethnographic research.